PERANCANGAN DAN SOSIALISASI SISTEM PENGAMAN INSTALASI LISTRIK PADA GEDUNG FASILITAS UMUM DI DESA PEKUTATAN JEMBRANA BALI - I.W.A Wijaya; I.G.N Janardana; C.G.I. Partha; I.N. Budiastra; I.B.A. Swamardika; I.W. Sukerayasa (Buletin Udayana Mengabdi, 2018)
design of electricity power installation, there are some items that have to be focused, one of them is thesecurity system design. In security system, accurate calculation is highly required to avoid dangers caused bythe usage of electricity power. One public facility that will be built in Pekutatan village is Wantilan. InWantilan, all villagers’ activities can be done. To support these activities, electricity installation must beinstalled. In order to correctly use the electricity, a design of security system is required to prevent dangerscaused by electricity failures. In designing electricity installation for Wantilan, it must refer to the PUIL2011. To answer the above issue, a public service to the villagers of Pekutatan village has been done. Thepublic service is composed by security system design, electricity power installation, security panelinstallation, and providing a tutorial about the danger of electricity and how to correctly use electricityenergy.